New estimates of the effects of minimum wages in the U.S. retail trade sector - John T. Addison; McKinley L. Blackburn; Chad D. Cotti (Institute for the Study of Labor (IZA), 2008)
This paper examines the impact of minimum wages on earnings and employment in selected branches of the retail-trade sector, 1990-2005, using county-level data on employment and a panel regression framework that allows for county-specific trends in sectoral outcomes. We focus on particular subsectors within retail trade that are identified as particularly low-wage. We find little evidence of disemployment effects once we allow for geographic-specific trends. Rather, in many sectors the evidence suggests modest (but robust) positive employment effects. One explanation we consider for these 'perverse' effects is that minimum wages may have significant influences on product demand shifts.
urn:nbn:de:101:1-2008072373
Keywords: J23; 330; Minimum wages; wages and employment; county-level data; spatial trends; border county analysis; unions; right-to-work states; Mindestlohn; Einzelhandel; Handelsberufe; Beschäftigungseffekt; Provinz; USA